2018
DOI: 10.18203/2320-6012.ijrms20181271
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of nasal lesions: 2 years study

Abstract: ackground: Majority of the nasal lesions are polypoid. It is difficult to comment upon the nature of the nasal lesion- whether neoplastic or non-neoplastic. Hence histopathological examination is essential for both ENT surgeons as well as pathologists. Aim to study the incidence of different nasal lesion. Also, to find out frequency of inflammatory, benign and malignant conditions of nasal lesions and to compare various histopathological lesions of nasal mass in relation to age, sex and site distribution.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
4
2
0
Order By: Relevance
“…Results obtained by Bakari et al showed a higher preponderance among the females than males which were in contrast to the present study [7]. In a study by Zafar et al [10], Parmar et al [14], and Kulkarni et al (2011), also male predominance was observed which was in accordance to the present study [9].…”
Section: Sinonasal Polypsupporting
confidence: 77%
See 1 more Smart Citation
“…Results obtained by Bakari et al showed a higher preponderance among the females than males which were in contrast to the present study [7]. In a study by Zafar et al [10], Parmar et al [14], and Kulkarni et al (2011), also male predominance was observed which was in accordance to the present study [9].…”
Section: Sinonasal Polypsupporting
confidence: 77%
“…In the present study, the peak was 3-6 decade of life and mostly unilateral which was in contrast to their study. Parmar et al also reported the most common age group for polyps 2-4 decade of life which was again dissimilar to the present study [14]. Regarding age group of nasal polyp, the study by Kulkarni et al (2020) observed the peak incidence in 3 rd decade which was in accordance with the present study [8].…”
Section: Sinonasal Polypsupporting
confidence: 76%
“…Adenoid cystic carcinoma was seen in 2.77% of our patients (Figure 4). Adenoid cystic carcinomas are more frequently encountered in such lesions and are aggressive tumors [11][12][13][14]. Two cases of malignant melanoma of the nose were also seen in our study, clinically presenting with a small mass in the vestibule (Figure 5).…”
Section: Figure 3: Inverted Papillomasupporting
confidence: 61%
“…Table 1 shows age wise distribution of the patients in the study population, Table 2 shows gender wise distribution of the study population and Table 3 shows clinical presentation of various nasal masses. 11 A histopathological study of total 100 cases of nasal lesions was done. Out of 100 cases, 59 were males and 41 were females.…”
Section: Resultsmentioning
confidence: 99%